Psoriasis patient preferences for topical drugs: a systematic review - Svendsen, Mathias Tiedemann; Feldman, Steven R.; Tiedemann, Sylvia Naiga; Sørensen, Anne Sofie Stochholm; Rivas, Cecilie Marie Ringgaard; Andersen, Klaus Ejner (The Journal of dermatological treatment, 2021)
Topical drugs are recommended first-line treatment for mild-to-moderate psoriasis. However, patient preferences for the topical drugs differ, since a wide variety of topical drugs and topical drug formulations are available. The aim of this study was to investigate psoriasis patient preferences for topical drugs. A systematic literature search was performed for English-language articles in Embase, Medline, PsycINFO, Cinahl, Scopus, and the Cochrane Library. Four surveys, six randomized controlled trials, and two prospective studies of mainly good quality were included. Seven of the studies investigated patient preferences for topical drug formulations, while five studies investigated their preferences for different topical drugs. Overall, patients preferred drugs that are easy to apply, less messy, and have a pleasant scent. Psoriasis patient preferences for topical drugs differ. There is no one topical drug or topical drug formulation that suits everyone, which shows the importance of individualized prescriptions for topical drugs that are based on shared decision-making between the prescriber and patient.